2017
DOI: 10.18632/oncotarget.16120
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant at the miRNA binding site in HMGB1 gene is associated with risk of oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a common malignancy that has been causally associated with both hereditary and acquired factors. The high mobility group box 1 (HMGB1) gene plays an important role as a DNA chaperone to help maintain nuclear homeostasis. Altered expression of HMGB1 has been implicated in a wide range of pathological processes, including inflammation and cancer. The present study explores the impact of HMGB1 gene polymorphisms, combined with environmental risks regarding susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Although polymorphism rs1360485 could not change the sequence of HMGB1 protein, it might regulate transcription process of HMGB1 or other gene. A series of studies have reported the association between polymorphisms rs1412125 or rs1360485 and the risk of cancers such as oral squamous cell carcinoma [ 27 ], hepatocellular carcinoma [ 31 ], uterine cervical neoplasia [ 33 ], colorectal cancer [ 34 ] as well as the lung cancer chemotherapy response [ 37 ]. Lin et al conducted a study to verify the association between four SNPs (rs1412125, rs2249825, rs1045411, and rs1360485) in HMGB1 and the risk of oral squamous cell carcinoma (OSCC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although polymorphism rs1360485 could not change the sequence of HMGB1 protein, it might regulate transcription process of HMGB1 or other gene. A series of studies have reported the association between polymorphisms rs1412125 or rs1360485 and the risk of cancers such as oral squamous cell carcinoma [ 27 ], hepatocellular carcinoma [ 31 ], uterine cervical neoplasia [ 33 ], colorectal cancer [ 34 ] as well as the lung cancer chemotherapy response [ 37 ]. Lin et al conducted a study to verify the association between four SNPs (rs1412125, rs2249825, rs1045411, and rs1360485) in HMGB1 and the risk of oral squamous cell carcinoma (OSCC).…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al conducted a study to verify the association between four SNPs (rs1412125, rs2249825, rs1045411, and rs1360485) in HMGB1 and the risk of oral squamous cell carcinoma (OSCC). They found that only the rs1045411 polymorphism could affect the risk of OSCC while other three SNPs might not be related to the susceptibility to OSCC [ 27 ]. Wu’s study showed an association of SNPs of HMGB1 with the risk of susceptibility to uterine cervical neoplasia for Taiwanese women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HMGB1 was suggested as a novel target for potential therapeutics since highly expressed HMGB1 was found to be associated with the epithelial-to-mesenchymal transition (EMT) and the overexpression of MMP-1, MMP-3, and MMP-10 via the RAGE/NF-κB signaling pathways, facilitating prostate cancer metastasis [ 1 , 16 , 17 , 18 , 19 , 20 ]. Furthermore, polymorphisms of HMGB1 have been associated with many cancers, including oral squamous cell carcinoma (OSCC) [ 21 , 22 ], lung cancer [ 23 , 24 , 25 , 26 ], breast cancer [ 27 , 28 , 29 ], gastric cancer [ 30 ], hepatocellular carcinoma (HCC) [ 31 , 32 ], and colorectal cancer (CRC) [ 33 ], and it was suggested that the SNPs of HMGB1 may provide a potential biomarker for predicting cancer risk, tumor development, or chemotherapy responses [ 21 , 25 , 27 , 31 ]. However, the impact of HMGB1 polymorphisms on prostate cancer susceptibility and clinicopathologic characteristics has remained uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have aimed to explore and uncover risk factors for developing OSCC. Genetic variation was highlighted in previous studies as a potential risk factor [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%